The effect of topical thiocolchicoside in preventing and reducing the increase of muscle tone, stiffness, and soreness: A real-life study on top-level road cyclists during stage competition - Gervasi, M.; Sisti, D.; Benelli, P.; Fernández-Peña, E.; Calcabrini, Ci.; Rocchi, M. B. L.; Lanata, L.; Bagnasco, M.; Tonti, A.; Stocchi, V.; Sestili, P. (Medicine, 2017)
In professional road cyclists, the majority of overuse injuries affect the lower limbs and are mostly represented by contractures or muscle shortening, characterized by an increase of tone and stiffness and a variation of elasticity. Treatment and prevention of these specific conditions may include physical, supplementary, and pharmacologic support. The aim of this real-life study was to determine: first, the alterations of tone, stiffness, elasticity, and soreness of rectus femoris (RF) and biceps femoris (BF) in top class cyclists engaged in 3 multistage races, and second, whether any variable in the management of the athletes may affect the prevention and/or reduction of such alterations.